Integrating The Bank’s Multicultural Framework Into The Islamic Religious Education Curriculum: The Qaṭ'ī-Ẓannī Epistemological Approach - Syifa Salsabila; Eko Puji Antoro; Alwi Hakim; Anita Setyarachma; Tri aprilia azmi (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
This study aims to formulate a theoretically grounded framework for integrating James A. Banks’ five dimensions of multicultural education into the Islamic Religious Education (PAI) curriculum in Indonesia. Using a qualitative-descriptive library research design, this study analyzes PAI curriculum documents including KMA No. 347/2022 and Banks’ foundational works through an integrative hermeneutic technique. The central contribution is the stratified epistemological compatibility framework, which resolves the tension between Banks’ secular-liberal epistemology and Islamic epistemic tradition by distinguishing between qaṭʻī (definitive, revelation-based) and ẓannī (interpretation-derived) knowledge. Banks’ dimensions are applicable at the ẓannī layer, enabling critical-inclusive pedagogy without compromising aqidah. This integration is anchored in Wasatiyyah and Ukhuwah Basyariyyah as indigenous theological foundations. Practically, this study recommends revising KMA No. 347/2022 operational guidelines, institutionalizing multicultural teacher training, and integrating digital literacy into PAI to counter exclusivist narratives. These findings contribute toward developing an adaptive PAI curriculum that fosters religious moderation within Indonesia’s pluralistic society.